Integrating Islamic Economic Principles with Circular Economy: A Case Study of Waste Management Innovation at Palakka Health Hope Community Self-Help Group - Ramlah, Sitti; Farida, Ida; S, Arifin (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2024)
This study examines the intersection of Islamic economic principles and circular economy concepts in waste management through an innovative case study of the Palakka Health Hope Community Self-Help Group (KSM). Using a qualitative descriptive approach enhanced by NVivo 12 software analysis, we conducted in-depth interviews with ten key stakeholders, including government officials, community members, and KSM personnel. The research reveals how KSM successfully implements circular economy principles through three key strategies: waste prevention, recycling initiatives, and cross-sector collaboration. Our analysis demonstrates that KSM's approach aligns with the Islamic concept of maslahah (public benefit) through its integration of environmental stewardship with economic development. The study identifies three fundamental Islamic economic principles - al-Ihsan (excellence), al-Kifayah (sufficiency), and al-Mas'uliyah (responsibility) - that harmonize with circular economy practices. The findings suggest that this integrated approach not only transforms waste into valuable resources but also creates sustainable employment opportunities while adhering to Islamic economic principles. This research contributes to the growing body of literature on faith-based approaches to environmental sustainability and provides practical insights for implementing religiously aligned circular economy initiatives in waste management.